PERTUMBUHAN DAN PRODUKSI PADI GOGO (Oryza sativa L. ) MELALUI APLIKASI BEBERAPA DOSIS ABU SEKAM PADI DAN PERBEDAAN KOMPOSISI PUPUK DI LAHAN GAMBUT - Sandy Perwira Sirait; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research was aimed to determine the effect of husk ash of rice and composition of fertilizer and its combination to increase growth and production of field rice and determine the best treatment dose of growth and production of field rice in peatland. The research was conducted at the experimental farm of the Agricultural Faculty University of Riau, Rimbo Panjang, Kampar from July to December 2016. The design used in this research are arranged in a Factorial Completely Randomized Block Design (RBD) consiting of two factor with three replication. The first factor are: Aplication of husk ash of rice (S), namely: S1 (2,5 tons/ha), S2 (5 tons/ha), S3 (7,5 tons/ha). and the second factor are: Composition of fertilizer, namely: K1 (Fertilizer Urea 200 kg/ha, TSP 100 kg/ha, KC 100 kg/ha), K2 (Fertilizer Urea 100 kg/ha TSP, 50 kg/ha, KCl 50 kg/ha) with coffee-based compost with chicken manure (3:1), K3 (Fertilizer Urea 100 kg/ha TSP, 50 kg/ha, KCl 50 kg/ha with coffee-based Compost with chicken manure (1:1), and K 4 (Fertilizer Urea 100 kg/ha TSP, 50 kg/ha, KCl 50 kg/ha) with coffee-based with chicken manure (3:1). The data obtained by analysis of variance (ANOVA) was tested further by Duncan’s New Multiple Range Test (DNMRT) at the level of 5%. The results showed that the combination treatment of rice husk ash 5 ton / ha and the composition of the fertilizer Urea, TSP, KCl (100,50,50 kg / ha) with with coffee-based compost with chicken manure (1: 1) showed better influence for maximum number of tiller, number of panicle / clump, number of grain per panicle, 1000 grain weight and dry weight of 344.52 g / m2 (3.34 ton / ha). The best rice husk ash treatment for upland rice plants is ash rice husk dose 7.5 tons / ha. The best composition of fertilizer and coffee-based compost for the upland rice plant is the composition of fertilizer Urea, TSP, KCl (100,50,50) kg / ha with coffee-based compost with chicken manure (1: 1)Keywords:Rice husk ash, Fertilizer Composition, Coffee-Based Compost with Chicken Manure